DIMENSI BUDAYA HOFSTEDE DAN REFLEKSINYA PADA PERJALANAN WISATA GENERASI Z : SEBUAH PENELUSURAN AWAL - Suasapha, Anom Hery (Paryaṭaka Jurnal Pariwisata Budaya dan Keagamaan, 2023)
To date, influence of Hofstede’s Cultural Dimension on generation Z tourist behavior is still unknown. This article seeks to explore indicators that can be used to measure reflection of Hofstede Cultural Dimension influence on tourism behavior of generation Z. Capitalizing on the indicators produced, this article also tries to understand the reflection of the Hofstede Cultural Dimension on Generation Z’s tourism behavior. To do so, data from 59 respondents were analyzed using item analysis and descriptive statistics. Result of item analysis shows there are 22 items that are considered valid as indicators to measure reflections of Hofstede Cultural Dimension. Meanwhile, result of descriptive statistics shows that when travelling, generation Z tend to have low power distance. They also in between collectivism and individualism, avoid uncertainty and are masculine. Given the exploratory nature of this research, it is recommended that the indicators to be used with bigger sample size to provide better understanding on the influence of Hofstede Cultural Dimension toward generation Z tourism behavior.